Synchronous liver and peritoneal metastases from colorectal cancer: Is cytoreductive surgery and hyperthermic intraperitoneal chemotherapy combined with liver resection a feasible option? - Di Carlo, Sara; Cavallaro, Giuseppe; La Rovere, Francesca; Usai, Valeria; Siragusa, Leandro; Izzo, Paolo; Izzo, Luciano; Fassari, Alessia; Izzo, Sara; Franceschilli, Marzia; Rossi, Piero; Dhimolea, Sirvjo; et al. (Frontiers in Surgery, 2022)
Background Traditionally, synchronous liver resection (LR), cytoreductive surgery (CRS), and hyperthermic intraperitoneal chemotherapy for colorectal liver and peritoneal metastases have been contraindicated. Nowadays, clinical practice has promoted this aggressive treatment in selected cases. This study aimed to review surgical and survival results of an extensive surgical approach including CRS with hyperthermic intraperitoneal chemotherapy (HIPEC) and LR. Methods PubMed, EMBASE, and Web of Science databases were matched to find the available literature on this topic. The search period was limited to 10 years (January 2010–January 2021). A threshold of case series of 10 patients or more was applied. Results In the search period, out of 114 studies found about liver and peritoneal metastases from colorectal cancer, we found 18 papers matching the inclusion criteria. Higher morbidity and mortality were reported for patients who underwent such an extensive surgical approach when compared with patients who underwent only cytoreductive surgery and HIPEC. Also, survival rates seem worse in the former than in the latter. Conclusion The role of combined surgical strategy in patients with synchronous liver and peritoneal metastases from colorectal cancer remains controversial. Survival rates and morbidity and mortality seem not in favor of this option. A more accurate selection of patients and more restrictive surgical indications could perhaps help improve results in this subgroup of patients with limited curative options.